STUDI KOMPARATIF METODE PEMURNIAN BENIH PADI, JAGUNG, DAN KEDELAI: DAMPAK TERHADAP HASIL PANEN DAN KUALITAS BENIH - Mela Susri Yuni; Meiwaldi Kesuma Dani; Henny Puspita Sari; Syamsuwirman (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This study aims to analyze the purity of rice, corn, and soybean seeds and the loss factor during the seed purification process. High seed purity is crucial for improving crop yields and agricultural product quality. The purification methods tested include manual sorting, machine cleaning, grading, optical technology, and drying. Analysis was conducted by weighing and separating seeds into pure seeds, other plant seeds, and seed impurities. The results show that rice seeds have the highest purity (95.84%) and the lowest loss factor (4.16%), followed by soybean (94.78% and 5.22%) and corn (94.43% and 5.57%). These findings indicate that modern purification technologies, such as optical technology, can significantly improve seed purity. The study recommends enhancing purification methods for corn to achieve better purity standards and considering the use of modern technology in seed purification processes generally to improve seed quality and crop yields..